Dinâmica do mercúrio total na área de influência da Usina Hidrelétrica de Curuá-Uma, Santarém-PA - PINTO, Yuryanne Carvalho (Universidade Federal do Oeste do Pará, 2021)
Mercury is a chemical element that presents high toxicity to living organisms. It bioaccumulates according to the weight and age of the individual, if it biomagnifies along the different trophic levels of the food chain, besides being transferred directly to the organism through the water. The present study aimed to investigate the dynamics of total mercury (HgT) in the UHE CuruáUna. Investigating the concentrations of HgT in muscular tissue of fish in different stretches in the UHE Curuá-Una; to verify the species that had concentrations within the limits allowed by WHO and ANVISA legislation; if the limnological variables influenced the concentrations of HgT and the bioconcentration of HgT in fish and periphyton in the different stretches in the UHE Curuá Una. The samples were collected in three different stretches (reservoir, transition and downstream) at UHE Curuá-Una, located in the western part of the state of Pará. All biological samples (water, fish and periphyton) were analyzed using the Atomic Fluorescence Cold Vapor (CVAFS). A total of 298 specimens were distributed in four species: Auchenipterus nuchalis (Spix & Agassiz, 1829) (n=58), Curimata knerii (Steindachnner, 1876) (n=62) and Hemiodus unimaculatus and Serrasalmus rhombeus (Linnaeus, 1766) (n=105). Only Hemiodus unimaculatus and Serrasalmus rhombeus showed significant differences between the different stretches, with H. unimaculatus presenting higher concentrations in the reservoir (150.24±96.26 ng.g1 ) and lower ones (78.40 ± 47.46 ng.g-1 ), and in S. rhombeus, the highest concentrations at the transition (427.45±245.51 ng.g-1 ) were observed, and the lower ones at the downstream (181.73 ± 76.18 ng.g-1 ). In the case of HgT concentrations, the upstream stretch (148.53±132.99 ng.g-1 ) was significantly different (H=23.46; p=0.0000) of the transition passages (292.47± 240.35 ng.g-1 ) and reservoir (249.52±232.36 ng.g-1 ). The concentrations of HgT between the trophic levels showed significant differences (H=136.30; p=0.000) between the concentrations of detritus feeding organisms (94.36±74.20 ng.g-1 ) and those of habit (324.97±245.61 ng.g-1 ) and insectivorous (338.26±203.04 ng.g-1 ), the latter two with higher concentrations. There was a significant difference in bioconcentration between trophic levels (H=81.93; p=0.00), demonstrating that the species that were at the lower trophic level of the trophic chain are bioconcentrating less (1.40±027 ng.g-1 ) than the top-chain species (2.01±0.32 ng.g-1 ). However, no significant differences were observed in the bioconcentration in the periphyton between the different stretches, but it was noteworthy to observe that the largest bioconcentration factor was transition (1.87 ng.g-1 ), followed by downstream (1.73 ng.g -1 ) and reservoir (1.62 ng.g-1 ) of the dam.